Skills of nurse needed for development of home care: reflection - Fernanda Catafesta; Maria Ribeiro Lacerda (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2008)
The reflexive test herein is to introduce the utmost competences which are necessary for the nurse home-care development. Being competent does not mean having a certain type of know how, but most importantly, is to know what to do with one's skills. When the scopes of providing specific professional services are put into practice, they can define and increase the value of the role of a nurse. Home-care service is part of an strategy focused on health, whose objective is attend to and assess, not only the client, but also their family and the context of their home. In order to develop this sort of care in a very efficient manner, there is the need for the professional, who is currently working in this area, to be able to develop an array of knowledge, skills and attitudes which are within necessary care requirements that will be provided to the clients and their family in their home (CAPES).